Industry 4.0 and the future of quality work in the global digital economy. (2nd January 2020) - Rainnie, Al; Dean, Mark
ABSTRACT: This paper engages with debates in academic literatures over Industry 4.0 (i4.0) and the Future of Work (FoW), critiquing their development in practical isolation from each other despite i4.0 recently coming to resemble in policymaking a widely adopted narrative for the FoW in the digital age. We argue that beyond their own individual inadequacies, both approaches have common failings. We conceptualise the role of i4.0 in shaping the FoW in terms of the development of global value chains and i4.0's implications for their digitalisation, where there is an underdeveloped analysis of change. We argue that the clearest expression of i4.0 is in the impact of 'platform capitalism', which already has implications for workers in the Global South and which, via i4.0's digital integration with production, will potentially have significant implications for the quality of work in the Global North.